PENGARUH PENERAPAN MODEL KOOPERATIF TIPE THINK PAIR SHARE BERBANTUAN GAME EDUKASI MATA PELAJARAN IPA TERHADAP HASIL BELAJAR SISWA DI SMPN 12 SOLOK SELATAN - Melisa Putri, Indah; Septriyan Anugrah; Rahmi Pratiwi; Alkadri Masnur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of implementing the cooperative learning model of the Think Pair Share (TPS) type assisted by educational games on students’ learning outcomes in science subjects for seventh-grade students at SMPN 12 Solok Selatan. The problems identified in the learning process include students’ low self-confidence in expressing opinions, lack of communication skills, and a tendency to be passive due to teacher-centered instruction dominated by lecture methods. These conditions have an impact on students’ low learning outcomes, which have not yet reached the Minimum Mastery Criteria (KKTP). This research is a quantitative study with a quasi-experimental approach. The population consisted of all seventh-grade students at SMPN 12 Solok Selatan, and the sampling technique used was total sampling. The sample included 22 students in the experimental class and 21 students in the control class. Data were collected through an objective test consisting of 20 validated items. Data analysis was conducted using normality tests, homogeneity tests, and an independent t-test. The results showed that the average learning outcome of students in the experimental class was 77.72, which is higher than that of the control class at 64.14. Based on the t-test, the value of t_calculated > t_table (3.2959 > 2.021) at a significance level of α = 0.05. Therefore, it can be concluded that the implementation of the Think Pair Share (TPS) cooperative learning model assisted by educational games has a significant effect on students’ learning outcomes in science subjects. Keywords: Think Pair Share, educational games, learning outcomes, science.